Combined spinal-epidural anaesthesia for urgent caesarean section in a parturient with Stevens-Johnson syndrome. (May 2017) - Ahiskalioglu, A.; Yayik, A.M.; Erguney, O.D.; Ahiskalioglu, E.O.; Alici, H.A.
Highlights: Anaesthesia for caesarean delivery in Stevens-Johnson syndrome is challenging. A multidisciplinary approach is essential in managing these patients. Combined spinal-epidural anaesthesia may be a suitable method.